High sensitivity C - reactive protein (hs-CRP) and clinical characteristics, endocrine, metabolic profile in Indian women with PCOS: a correlation - Ramanand, Sunita Jaiprakash; Ramanand, Jaiprakash B.; Raparti, Girish T.; Ghanghas, Ravi R.; Halasawadekar, Nimish R.; Patil, Praveenkumar T.; Pawar, Mayur P. P.; Shinde, Mayur P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Role of hs-CRP was studied in PCOS women. Methods: Correlation between serum hs-CRP and endocrine, metabolic profile was studied in 30 healthy women and 88 PCOS women. In PCOS women correlation between hs-CRP and clinical characteristics viz obesity, infertility, acne, hirsutism, acanthosis nigricans (AN) was also studied. Serum levels of hs-CRP, Luteinizing hormone (LH), Follicle stimulating hormone (FSH), LH:FSH ratio, Testosterone (Testo), fasting insulin, fasting blood glucose (FBG), total cholesterol (TC), triglyceride (Tg), low density lipoprotein (LDL), high density lipoprotein (HDL) and Homeostasis Model Assessment (HOMA) were estimated. Results: Mean serum hs-CRP in PCOS women was higher than that in control women (6.9 ± SE 0.84 v/s 2.0 ± SE 0.19mg/L, P=0.005). In PCOS group overweight/obese had higher hs-CRP as compared to normal weight women (P=0.0051). In control group hs-CRP was positively correlated with age (r=0.385 p=0.035) and LDL (r=0.38 P=0.036). PCOS women showed positive correlation between hs-CRP and cholesterol, LDL, fasting insulin, HOMA. PCOS women showed a significant negative correlation between hs-CRP and LH. AN positive PCOS women showed higher serum hs-CRP levels as compared to AN negative PCOS women (11 ± SE 0.7 v/s 5.5 ± SE 2.3, P=0.0439). Conclusions: Serum hs-CRP is raised in Indian PCOS women reflecting association of low grade chronic inflammation. A positive correlation is present between hs-CRP and AN, insulin in PCOS women and obesity may aggravate this association. A positive correlation between hs-CRP and TC, LDL in the background of normal lipid profile is suggestive of precedence of chronic inflammation over dyslipidemia in PCOS.